Transplantation of inbred adipose‐derived stromal cells in rats with plasma gel containing fragmin/protamine microparticles and FGF‐21. Issue 5 (29th January 2013) - Sumi, Yuki; Ishihara, Masayuki; Kishimoto, Satoko; Takikawa, Megumi; Doumoto, Takashi; Azuma, Ryuichi; Nakamura, Shingo; Hattori, Hidemi; Fujita, Masanori; Kiyosawa, Tomoharu
Abstract: Fragmin/protamine microparticles (F/P MPs) have been used as a cell carrier for adipose‐derived stromal cells (IR‐ASCs) in inbred male Fisher 344 rats, and for preservation and controlled‐release of fibroblast growth factor (FGF)‐2 and various cytokines in inbred rat plasma (IRP)‐DMEM (Dulbecco's modified Eagle's medium) gel. In this study, we investigated the capability of an IRP‐DMEM gel containing F/P MPs and/or FGF‐2, as a three‐dimensional (3D)‐culture, to expand IR‐ASCs. We found that IR‐ASCs grow faster under 3D‐culture conditions in low IRP (3%)‐DMEM gel containing F/P MPs and FGF‐2 without any animal serum than those under 2D‐culture in low inbred rat serum (3%)‐DMEM with F/P MPs and FGF‐2. About 0.3 mL of IR‐ASCs (about 4, 000, 000 cells mL −1 ) grown in IRP (6%)‐DMEM gel containing F/P MPs and FGF‐2 disappeared 8 days after subcutaneous injection in rats, suggesting that they are rapidly biodegradable. The number of large (diameter ≥200 μm or containing ≥100 erythrocytes), medium (diameter = 20–200 μm or containing 10–100 erythrocytes) and small (diameter ≤20 μm or containing 1–10 erythrocytes) capillaries after injection with IR‐ASCs in an IRP‐DMEM gel containing both F/P MPs and FGF‐2, as well as the thickness of tissue granulation per microphotograph at the injected site, was significantly higher than those after injection with IR‐ASCs in an IRP‐DMEM gel containing either FGF‐2 or F/P MPs. Thus, IRP‐DMEM gel containing F/P MPs and FGF‐2 are useful and safe IR‐ASC carriers that facilitate cell proliferation, vascularization, and tissue granulation locally at injection sites. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.